1999
DOI: 10.1149/1.1391642
|View full text |Cite
|
Sign up to set email alerts
|

Vanadyl Precursors Used to Modify the Properties of Vanadium Oxide Thin Films Obtained by Chemical Vapor Deposition

Abstract: Vanadium oxide thin films were prepared by chemical vapor deposition using as precursors a series of vanadyl complexes of general formula VO(L) 2 (H), where L is a ␤-diketonate ligand. The depositions were carried out on ␣-Al 2 O 3 subtrates in O 2 , N 2 , and N 2 ϩ H 2 O atmospheres. In order to elucidate the role played by different ligands and synthesis conditions on the properties of the obtained films, the chemical composition of the samples was investigated by X-ray photoelectron spectroscopy, while thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(43 citation statements)
references
References 11 publications
4
35
0
Order By: Relevance
“…Both VO2(B) and V2O5 are usually considered to be n-type semiconductors at room temperature [58][59][60] . This was confirmed for the CHFS produced VO2 materials under investigation in the current study using the hot-probe method (Fig.…”
Section: P-type Sensing Responsesmentioning
confidence: 99%
See 1 more Smart Citation
“…Both VO2(B) and V2O5 are usually considered to be n-type semiconductors at room temperature [58][59][60] . This was confirmed for the CHFS produced VO2 materials under investigation in the current study using the hot-probe method (Fig.…”
Section: P-type Sensing Responsesmentioning
confidence: 99%
“…For p-type materials, electron donation reduces the number of holes (the majority charge carriers), resulting in a p-type increase in device resistance 12 . However, as discussed in the previous section, VO2 is normally considered to be an n-type semiconductor at room temperature [58][59][60] . Once again, the formation of a surface inversion layer would explain the anomalous p-type responses of the VO2 based sensors toward NH3.…”
Section: Sensitivity To Ammonia Gasmentioning
confidence: 99%
“…• C, in O 2 , N 2 and N 2 and H 2 O atmospheres (Barreca et al 1999). Also, vanadium acetylacetonate V[C 5 H 7 O 2 ] 3 has been used in a spray pyrolysis process in a controlled atmosphere to produce vanadium oxide films (VO 2 , V 2 O 3 and V 2 O 5 ) (Sahana et al 2002b).…”
Section: Chemical Vapour Depositionmentioning
confidence: 99%
“…• C to convert it from the meta-stable phase to the metallic rutile phase (Barreca et al 1999). Atmospheric pressure chemical vapour deposition (APCVD) has been used to produce thin films directly .…”
Section: Chemical Vapour Depositionmentioning
confidence: 99%
“…The transition tempera-ture has also been shown to be affected by film strain [11] and it has been demonstrated that strain can be introduced by careful choice of deposition conditions [12]. Tungsten doped vanadium dioxide films have been prepared by a variety of methods including physical vapour deposition [13], sol-gel [14], and chemical vapour deposition (CVD) methodologies [15][16][17]. CVD routes to the production of VO 2 films are generally considered more attractive because of the ability to integrate CVD processes with high volume float glass manufacture and the physical properties of CVD produced films, which are generally adherent and durable [18].…”
Section: Introductionmentioning
confidence: 99%